TCNQ Physisorption on the Topological Insulator Bi2Se3. Issue 18 (19th June 2018) - Pia, Ada Della; Lisi, Simone; Luca, Oreste De; Warr, Daniel A.; Lawrence, J.; Otrokov, Mikhail M.; Aliev, Ziya S.; Chulkov, Evgueni V.; Agostino, Raffaele G.; Arnau, Andrés; Papagno, Marco; Costantini, Giovanni
Abstract: Topological insulators are promising candidates for spintronic applications due to their topologically protected, spin‐momentum locked and gapless surface states. The breaking of the time‐reversal symmetry after the introduction of magnetic impurities, such as 3d transition metal atoms embedded in two‐dimensional molecular networks, could lead to several phenomena interesting for device fabrication. The first step towards the fabrication of metal‐organic coordination networks on the surface of a topological insulator is to investigate the adsorption of the pure molecular layer, which is the aim of this study. Here, the effect of the deposition of the electron acceptor 7, 7, 8, 8‐tetracyanoquinodimethane (TCNQ) molecules on the surface of a prototypical topological insulator, bismuth selenide (Bi2 Se3 ), is investigated. Scanning tunneling microscope images at low‐temperature reveal the formation of a highly ordered two‐dimensional molecular network. The essentially unperturbed electronic structure of the topological insulator observed by photoemission spectroscopy measurements demonstrates a negligible charge transfer between the molecular layer and the substrate. Density functional theory calculations confirm the picture of a weakly interacting adsorbed molecular layer. These results reveal significant potential of TCNQ for the realization of metal‐organic coordination networks on the topological insulator surface. Abstract : The adsorption of the prototypical molecular electron acceptor TCNQ on the Bi2 Se3 topological insulator is studied. Scanning tunneling microscopy and photoemission spectroscopy studies combined with density functional theory calculations reveal a negligible charge transfer and an essentially unperturbed electronic structure of the substrate, outlining an overall physisorption picture. The results reveal a significant potential of TCNQ for the realization of metal‐organic coordination networks on topological insulator surfaces.